IMPROVING BIOLOGICAL SCIENCE LEARNING OUTCOMES WITH USED A CONTEXTUAL-BASED INQUIRY APPROACH THE CONCEPT OF PHOTOSYNTHESIS IN CLASS VIII STUDENTS OF JUNIOR HIGH SCHOOL NEGERI 2 AMBON - Wattimury, Ince; Arini, Ine; Smith, Alwi (Universitas Pattimura, 2023)
The inquiry approach is one of the approaches proposed by experts to be developed in the learning process. Where inquiry learning teaches students how to research problems or questions of facts. Learning used an inquiry approach requires a classroom environment where students feel free to create, make assumptions and draw conclusions. The aim of this research is to determine the improvement in biological science learning outcomes regarding the concept of photosynthesis used a contextual-based inquiry learning approach for class VIII3 students at Junior Hight School Negeri 2 Ambon. This type of research includes descriptive research using a PTK design. This research was conducted at a Junior High School Negeri 2 Ambon. The subjects in this research were students in class VIII3 as many as 26 students. Data analysis uses qualitative data, then the final value is converted using completeness criteria. Based on the tests gived in cycle I, the final test results for each group were not significant. In group I, only 4 students (15.4%) had not reached the completion criteria and 5 other students were able to achieve completion with a percentage (19.2%). The number of students who achieved completeness in group II was 7 students (27.0%), and 2 other students (7.7%) did not achieve completeness. Meanwhile in group III, there were 5 students who were able to achieve completeness with a percentage of (19.2%) and 3 students (11.5%) who did not achieve completeness. Thus, there were 9 students (34.6%) who had not achieved completeness and 17 students (65.4%) had achieved completeness. Meanwhile, in cycle II the test results increased. In group I, there were 5 students who met the completion criteria with a percentage of 19.2%, 4 other students still had not completed it. Group II increased even more, 7 students (27%) met the criteria for completion while 2 students (7.7%) still did not complete. In group III there were 5 students (19.2%) who met the criteria for completion, and 3 other students (11.5%) who still had not completed it. The final test seems to show very good results. The conclusion of the research was taught used a contextual-based inquiry approach to the concept of photosynthesis can improve student learning outcomes, seen in cycle I and cycle II because the cognitive, affective and psychomotor aspects can improved.